2012
DOI: 10.4103/2278-330x.103715
|View full text |Cite
|
Sign up to set email alerts
|

Post-chemotherapy arthralgia and arthritis in lung cancer

Abstract: Objective:Evaluate the characteristics of arthritis, arthralgia and musculoskeletal pain after chemotherapy in patients with lung cancer.Materials and Methods:In this study, we evaluate the characteristics of 17 patients with joint symptoms following receiving chemotherapy for lung cancer. Demographic information of patients including sex, age, time of rheumatologic findings after starting of chemotherapy, time of improvement after starting of medication, and relevant laboratory findings for each patient.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Subsequent studies have also reported a short period of time (~3–8 months) before the onset of symptoms 6,8,9. However, the patients in our series presented with symptoms of arthralgia at widely varying time points after the initiation of chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Subsequent studies have also reported a short period of time (~3–8 months) before the onset of symptoms 6,8,9. However, the patients in our series presented with symptoms of arthralgia at widely varying time points after the initiation of chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier studies5,6,8,9,11 have reported variable response rates to treatment with non-steroidal anti-inflammatory drugs or disease-modifying antirheumatic drugs. In our series, none of our patients were prescribed NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations